Dynamical Systems and Random Processes - Hawkins, Jane (Contemporary Mathematics Ser., 2019)
This volume contains the proceedings of the 16th Carolina Dynamics Symposium, held from April 13-15, 2018, at Agnes Scott College, Decatur, Georgia. The papers cover various topics in dynamics and randomness, including complex dynamics, ergodic theory, topological dynamics, celestial mechanics, symbolic dynamics, computational topology, random processes, and regular languages. The intent is to provide a glimpse of the richness of the field and of the common threads that tie the different specialties together.